Single-pixel terahertz imaging: a review - Zanotto Luca (Institue of Optics and Electronics, Chinese Academy of Sciences, 2020)
This paper is devoted to reviewing the results achieved so far in the application of the single-pixel imaging technique to terahertz (THz) systems. The use of THz radiation for imaging purposes has been largely explored in the last twenty years, due to the unique capabilities of this kind of radiation in interrogating material properties. However, THz imaging systems are still limited by the long acquisition time required to reconstruct the object image and significant efforts have been recently directed to overcome this drawback. One of the most promising approaches in this sense is the so-called "single-pixel" imaging, which in general enables image reconstruction by patterning the beam probing the object and measuring the total transmission (or reflection) with a single-pixel detector (i.e., with no spatial resolution). The main advantages of such technique are that i) no bulky moving parts are required to raster-scan the object and ii) compressed sensing (CS) algorithms, which allow an appropriate reconstruction of the image with an incomplete set of measurements, can be successfully implemented. Overall, this can result in a reduction of the acquisition time. In this review, we cover the experimental solutions proposed to implement such imaging technique at THz frequencies, as well as some practical uses for typical THz applications.